"Why Don't You Go Into Suburbs? Why Are You Targeting Us?": Trust and Mistrust in HIV Vaccine Trials in South Africa. (December 2018) - Thabethe, Siyabonga; Slack, Catherine; Lindegger, Graham; Wilkinson, Abigail; Wassenaar, Douglas; Kerr, Philippa; Bekker, Linda-Gail; Mngadi, Kathy; Newman, Peter A.
Trust is a key element of high-quality stakeholder relations, which are themselves essential for the success of HIV vaccine trials. Where trust is absent, community stakeholders might not volunteer to become involved in key trial activities, and potential participants might not volunteer for enrollment. We explored site staff and Community Advisory Board (CAB) members' experiences of trust/mistrust among community members and potential participants. We analyzed 10 focus group discussions with site staff and CAB members at two active South African HIV vaccine trial sites. We report on key characteristics perceived to contribute to the trustworthiness of communicators, as well as factors associated with mistrust. Attributes associated with trustworthy communicators included shared racial identity, competence, and independence (not being "captured"). Key foci for mistrust included explanations about site selection, stored samples, vaccination, and Vaccine Induced Sero-Positivity (VISP). Our findings suggest that community members' trust is not necessarily global, in which trials are trusted or not; rather, it appears fairly nuanced and is impacted by various perceived attributes of communicators and the information they provide. We make recommendations for clinical trial site stakeholders invested in building trust and for future research into trust at these sites.